The Predictability of Stock Market Regime: Evidence from the Toronto Stock Exchange - van Norden, Simon; Schaller, Huntley (The Review of Economics and Statistics, 1993)
Simon van Norden, Huntley Schaller, The Predictability of Stock Market Regime: Evidence from the Toronto Stock Exchange, The Review of Economics and Statistics, Vol. 75, No. 3 (Aug., 1993), pp. 505-510